Anaphylaxis After Immunization of Children and Adolescents in Germany. Issue 5 (May 2016) - Oberle, Doris; Pavel, Jutta; Rieck, Thorsten; Weichert, Stefan; Schroten, Horst; Keller-Stanislawski, Brigitte; Tenenbaum, Tobias
Abstract : Background: Anaphylaxis is a life-threatening event. The aim of this study was to estimate the annual frequency of anaphylaxis after immunization in individuals younger than 18 years in Germany leading to hospitalization. Methods: All suspected cases of postvaccination anaphylaxis involving individuals aged 0−17 years reported to the German surveillance unit for rare pediatric diseases (Erhebungseinheit für seltene pädiatrische Erkrankungen in Deutschland) from June 2008 through May 2010, and all suspected cases of anaphylaxis as an adverse event following immunization in the same age group reported to the Paul-Ehrlich-Institut during the observational period were classified according to the Brighton collaboration case definition. Only hospitalized cases of anaphylaxis fulfilling Brighton collaboration case definition level 1–3 criteria were eligible. Estimates for the annual frequency were calculated by using capture–recapture methods. Results: A total of 22 reports were eligible. Median age of the affected individuals (13 males, 9 females) was 7.0 years (range: 2 months to 17 years). Anaphylaxis occurred most frequently after administration of AS03 adjuvanted A/H1N1 pandemic influenza vaccine (n = 8). The annual frequency of anaphylaxis after vaccination (excluding pandemic influenza vaccine as well as monovalent measles and rubella vaccines) was estimated to be 6.8 (95% confidence interval: 6.1–10.9). The estimated incidence of anaphylaxis after administration of specific vaccines ranged from 0.4 to 127.6 cases per 1, 000, 000 doses administered. Conclusions: This study confirms that anaphylaxis after immunization in children and adolescents is a rare event. AS03 adjuvanted A/H1N1 pandemic influenza vaccine seems to be associated with a higher risk of anaphylaxis when compared with other vaccines. Abstract : Supplemental Digital Content is available in the text.